2016
DOI: 10.1159/000445589
|View full text |Cite
|
Sign up to set email alerts
|

MiR-221 Promotes Capan-2 Pancreatic Ductal Adenocarcinoma Cells Proliferation by Targeting PTEN-Akt

Abstract: Background/Aims: MicroRNAs (miRNAs, miRs) have emerged as critical regulators of cancer cell proliferation. The effect of miR-221 on cancer cell growth could be significantly changeable in different cell lines. Although miR-221 was reported to promote the cell growth of pancreatic ductal adenocarcinoma (PDAC) cells, its role in Capan-2 cell line is largely unknown. Methods: Capan-2 cells were transfected with miR-221 mimics, inhibitors, or negative controls. Cell Counting Kit-8 was used to determine cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…In human umbilical vein endothelial cells, miR-221 is found to inhibit autophagy by modulating a PTEN/Akt signaling pathway (12). miR-221 targeting PTEN/Akt is also reported in several cancer cells during cancer development (33)(34)(35). Our results implicated a potential role of TP53INP1 on the effect of miR-221 on autophagy of CRC.…”
Section: Discussionsupporting
confidence: 64%
“…In human umbilical vein endothelial cells, miR-221 is found to inhibit autophagy by modulating a PTEN/Akt signaling pathway (12). miR-221 targeting PTEN/Akt is also reported in several cancer cells during cancer development (33)(34)(35). Our results implicated a potential role of TP53INP1 on the effect of miR-221 on autophagy of CRC.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies showed that miR-221 was overexpressed in PaCa tissues and associated with distant metastasis [53,54], which suggested that this miRNA might serve as a biomarker for the diagnosis of PaCa [55]. In addition, it was reported that miR-221/222 induced the expression of matrix metalloproteinase-2 (MMP-2) and MMP-9 [56], targeting the phosphatase and tensin homolog-protein kinase B (PTEN-Akt) pathway [57]. In pancreatic cells, miR-221 was essential for the PDGF-mediated EMT phenotype [58], and overexpression of mir-221-3p promoted 5-FU resistance [59].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, a large number of microRNAs (miRNAs) have been shown to be potentially effective in the treatment of malignancies [6][7][8][9]. MiRNAs are a group of endogenous evolutionarily conserved small non-coding RNAs, which have been proven to be essential in the development of PDAC, including cell proliferation, cell death, differentiation, angiogenesis, migration, metabolism, and invasion [6,10,11].…”
Section: Introductionmentioning
confidence: 99%